Failure analysis of flow-induced vibration problem of in-serviced duplex stainless steel piping system in oil and gas industry. (8th December 2014) - Kong, K. K.; Khoo, S. Y.; Ong, Z. C.; Eng, H. C.; Ismail, Z.; Chong, W. T.; Noroozi, S.; Rahman, A. G. A.
<x content-type="archive" xml:space="preserve">Abstract</x> Failure of the duplex stainless steel piping system in oil and gas industry can have disastrous effects. In this study, a novel method of failure analysis of flow-induced vibration problem of in-serviced duplex stainless steel piping system is proposed. The proposed non-destructive technique is able to determine a suitable operating condition for continuous operation without failure. The technique relies on the combined operation of operational modal analysis, operating deflection shape analysis and linear elastic finite element analysis. The effect of different operating conditions for two distinct valve opening cases (i.e. fully opened and partially opened) on the dynamic stress is examined, and they are utilised for forecasting purpose in failure analysis. The result shows that maximum operating conditions are 360 and 400 mmscfd for fully opened and partially opened flow control valves, respectively. Beyond this limit, the piping system most likely will fail.